GENDER MAINSTREAMING PLAN FOR GENDER-RESPONSIVE PUBLIC SCHOOLS: Received: 25th May 2021; Revised: 15th August 2021, 10th January 2022, 19th January 2022; Accepted: 20th January 2022 - Duma, Michelle G (PUPIL: International Journal of Teaching, Education and Learning, 2022)
This study sought to develop a gender mainstreaming plan for gender-responsive public schools. Specifically, the extent of gender mainstreaming practices among public schools and their hindering factors were assessed in this research. A descriptive method of research was employed to investigate the posed objectives in this study. Purposive and random sampling techniques were utilized in the selection of the respondents. Guided by the said sampling procedures, 282 school heads participated in the study. Data were collected through survey-questionnaire and computed using the weighted arithmetic mean (WAM). Results indicated that gender perspectives are relatively mainstreamed in the organizational processes of public schools. Specifically, gender perspectives are less mainstreamed into the policies and PPAs but relatively integrated into their support mechanisms and highly evident among people. However, lack of gender analysis and gender mainstreaming plan, as well as insufficient knowledge and training of internal and external clients are highly hindering factors among public schools to implement gender mainstreaming. Based on the results of this study, a gender mainstreaming plan was developed to serve as a framework among public schools in mainstreaming gender perspectives on their policies, PPAs, and enabling mechanisms.